A new design of variable optical attenuator based on multimode interference coupler - Mustafa M. Khalifa Jabiry, 1984-; Mohd. Haniff Ibrahim; Fakulti Kejuruteraan Elektrik (2009)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2009